WWP1 targeting PTEN for polyubiquitination to promote bone metastasis of luminal breast cancer - Hao Jiang; Zhenxi Li; Wei Xu; Jianru Xiao (Scientific Reports)
Abstract Luminal breast cancer exhibits a high incidence of bone recurrence when metastasizing to distant organs. The mechanisms underlying the organotropism of luminal breast cancer cells remain unclear. In this study, we aimed to determine the role of WWP1 (WW domain-containing E3 ubiquitin protein ligase 1)-PTEN (phosphatase and tensin homolog deleted on chromosome ten) interaction in bone tropism in luminal breast cancer. We observed that WWP1 was overexpressed in luminal breast cancer tissues and associated with poor prognosis in breast cancer patients. In luminal breast cancer cells, WWP1 was found to mediate PTEN ubiquitination, resulting in the functional loss of PTEN. As a result, we demonstrate that WWP1 contributes to bone tropism in luminal breast cancer cells via the polyubiquitination of PTEN. Consequently, WWP1-mediated PTEN polyubiquitination contributed to the early metastasis of luminal breast cancer cells to the bone. Thus, our study provides a mechanistic insight into the bone tropism of luminal breast cancer cells and proposes a potential therapeutic strategy for mitigating cancer metastasis to the bone.